Visual core description of IODP Hole 386-M0095A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Collection of visual core description (VCD) sheets (hand drawn originals and digital representations) and lithologic composite plots from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). VCD was performed on unsampled archive halves of split cores, directly after linescan imaging, during the onshore phase of expedition 386, which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu. The lithology of each core section is represented on the hand drawn VCDs by graphic patterns next to the X-ray CT image of the archive-half core section. Further, a wide variety of features that characterize the sediment are indicated in additional columns. The information from the hand-drawn VCD sheets was then transferred into the Drilling Information System database (s. also datasets "Description of lithologic section units of IODP Hole 386-M0095A"), from where it could be accessed semi-automated to produce digital lithologic columns and composite plots using Strater (Golden Software). For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023